Proceedings of the 1st Economics and Business International Conference 2017 (EBIC 2017) 2018
DOI: 10.2991/ebic-17.2018.27
|View full text |Cite
|
Sign up to set email alerts
|

The Factors Which Influence Accounting Students Understanding with Spiritual Intelligence as Moderating Variable (An Empirical Study on the student of USU, UNIMED, and UINSU)

Abstract: The objective of the research was to analyze the factors influencing accounting students to understand accounting with spiritual quotient as the moderating variable (an empirical study on Students of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 1 publication
1
1
0
3
Order By: Relevance
“…The desire to progress from within students will generate enthusiasm in improving self-quality. The results of this study are also in line with research conducted by Research conducted by Listya & Bakar [19] and Hayati & Wulandari [20] found that learning motivation has an effect on the level of student accounting understanding.…”
Section: The Effect Of Learning Motivation On the Level Of Accounting...supporting
confidence: 91%
See 1 more Smart Citation
“…The desire to progress from within students will generate enthusiasm in improving self-quality. The results of this study are also in line with research conducted by Research conducted by Listya & Bakar [19] and Hayati & Wulandari [20] found that learning motivation has an effect on the level of student accounting understanding.…”
Section: The Effect Of Learning Motivation On the Level Of Accounting...supporting
confidence: 91%
“…Learning motivation is the driving force within the individual that can spur learning activities, as well as ensure the continuity of learning activities and provide direction to learning activities, so that goals can be achieved [18]. Research conducted by Listya & Bakar [19] and Hayati & Wulandari [20] found that learning motivation had a significant positive effect on students' accounting comprehension levels. However, this is not in line with the results of research by Afandi [21] and Matapere & Nugroho [22] which found that learning motivation had no effect on the level of students' accounting understanding.…”
Section: Introductionmentioning
confidence: 99%
“…Mahasiswa yang memiliki perilaku belajar yang baik akan berusaha untuk mempersiapkan bahan yang akan dipelajari sebelum memasuki kelas, selalu mengulang materi yang dipelajari dengan banyak membaca dan mengerjakan latihan soal, berpartisipasi dalam diskusi di kelas, aktif bertanya ketika mengalami kesulitan dalam belajar, dan percaya diri ketika menghadapi ujian dengan tidak melakukan kecurangan dalam ujian. Hasil penelitian-penelitian sebelumnya menunjukkan bahwa perilaku belajar berpengaruh positif terhadap tingkat pemahaman akuntansi (Sari et al, 2017;Laksmi & Febrian, 2018;Sari & Sartika, 2018;Listya et al, 2017). Maryati (2017) dan Rahayu (2019) menemukan hal yang sebaliknya yaitu perilaku belajar tidak berpengaruh terhadap tingkat pemahaman akuntansi.…”
Section: Abstrakunclassified
“…Perilaku belajar yang baik akan menjadikan mahasiswa berpartisipasi aktif di kelas, rajin mengerjakan latihan soal tanpa diperintah oleh dosen, terus berupaya belajar hingga dapat memahami suatu ilmu, rajin membaca, membuat catatan dan memahaminya, mengulangi kembali apa yang sudah dipelajari, selalu berkunjung ke perpustakaan, dan selalu berusaha agar memiliki buku sendiri untuk dipelajari. Penelitian yang dilakukan oleh Suprianto & Harryoga (2015), Agustina & Yanti (2015), Listya et al (2017), Sari et al (2017), Laksmi & Febrian (2018), Nugroho et al (2018), Sari & Sartika (2018) menunjukkan bahwa perilaku belajar berpengaruh positif terhadap tingkat pemahaman akuntansi. Maryati (2017) dan Rahayu (2019) menemukan hasil yang berbeda yaitu perilaku belajar tidak berpengaruh terhadap tingkat pemahaman akuntansi.…”
Section: Abstrakunclassified
See 1 more Smart Citation